Simulation Studies of Diffserv Policies for the Internet Traffic - Audah, L.; Jusoh, N.; Jamil, A.; Abdullah, J.; Hamzah, S.A.; Alduais, N.A.M.; Razak, M.A.A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Differentiated Services (Diffserv) is the Internet architecture that uses the queuing management schemes to provision the traffic flows in the Internet backbone system. It discriminates traffic flows to a finite aggregate of classes and provides scalability solution by simplifying the complexity functions at the edge routers. In this paper, we study the end-toend (e2e) Quality of Service (QoS) performance of File Transfer Protocol (FTP) and Constant Bit Rate (CBR) traffics transmitted over a Diffserv network. The Diffserv system applied the Token Bucket, Time Sliding Window Three Color Marker (TSW3CM) and Single Rate Three Color Marker (SRTCM) traffic provisioning policies. The e2e QoS parameters include delay, jitter, loss ratio and throughput are analyzed and compared among the policy types against the increment of traffic connections in the network system. We conclude that the FTP traffic could achieved the best overall delay performance using SRTCM policy and the best jitter performance using TSW3CM. The lowest overall loss ratio and the best throughput for FTP could be achieved using Token Bucket. Besides that, the CBR traffic has achieved the best overall delay performance using TSW3CM policy while the SRTCM policy provides the best jitter, loss ratio and throughput performances. The future works aims to design the combination of QoS aware routing, scheduling, and Diffserv queuing schemes that can adaptively maintain QoS for each type of traffic at optimum level.